2009
DOI: 10.1089/ten.tec.2008.0410
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Adherent Cells: Strategies to Improve Cell Viability and Function After Thawing

Abstract: The commonly applied cryopreservation protocols routinely used in laboratories worldwide were developed for simple cell suspensions, and their application to complex systems, such as cell monolayers, tissues, or biosynthetic constructs, is not straightforward. In particular for monolayer cultures, cell detachment and membrane damage are often observed after cryopreservation. In this work, combined strategies for the cryopreservation of cells attached to Matrigel-coated well plate's surfaces were investigated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 75 publications
(60 reference statements)
3
27
0
Order By: Relevance
“…First, we evaluated survival of HeLa, NIH3T3, and MCF-7 cells after cryopreservation. In contrast, the low survival rates on the control culture dishes are consistent with previous papers (Malpique et al, 2009;McKay et al, 2002;Miyamoto et al, and the ready-to-use (lower) cell-based experimental platforms. In the same sampling area of the cell culture zone, live (PI negative and Hoechst positive) cells and dead (PI positive) cells were counted.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…First, we evaluated survival of HeLa, NIH3T3, and MCF-7 cells after cryopreservation. In contrast, the low survival rates on the control culture dishes are consistent with previous papers (Malpique et al, 2009;McKay et al, 2002;Miyamoto et al, and the ready-to-use (lower) cell-based experimental platforms. In the same sampling area of the cell culture zone, live (PI negative and Hoechst positive) cells and dead (PI positive) cells were counted.…”
supporting
confidence: 90%
“…One conclusion of these studies is that the adhered cells are more susceptible to cryoinjury than suspended cells. To cut this lengthy incubation process, considerable effort has been made to cryopreserve cells in the adhered state (Malpique et al, 2009;McKay et al, 2002;Miyamoto et al, 2009;Shoji et al, 2007). In a conventional protocol, the cryopreserved cells are thawed, washed, and seeded onto a dish surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we recently demonstrated that cell encapsulation in alginate is a valuable strategy for improving cell viability and the integrity of cell monolayers and neurospheres after freeze/thawing, since cells are protected against mechanical damages during ice crystallization and the risk of disrupting cell-cell and cell-matrix contacts are reduced through immobilization within the hydrogel [29], [30]. Despite such success in many (stem) cell types, studies describing the microencapsulation of hESCs are still limited [12], [25], [31].…”
Section: Introductionmentioning
confidence: 99%
“…Different transportation strategies have been investigated [30] and a significant amount of research has been carried out to understand the effects of cold storage and cryopreservation on the viability of cells [31][32][33]. The study carried out within the research reported here has investigated the effects of the combination of cold storage and mechanical stress during cold transport of an hMSC suspension without the presence of cryoprotectant.…”
Section: Discussionmentioning
confidence: 99%